2000
DOI: 10.1177/089033440001600303
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Breastfeeding Initiation in Adolescent Mothers Through the Breastfeeding Educated and Supported Teen (BEST) Club

Abstract: The purpose of this study was to determine if specific breastfeeding education, provided by a lactation consultant in group classes for pregnant adolescents, would increase breastfeeding initiation among students enrolled in a high school adolescent pregnancy program. Ninety-one pregnant adolescents participated in the study and were divided into two groups: those who did not receive specific breastfeeding education and those who did, through the Breastfeeding Educated and Supported Teen (BEST) Club. There wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
91
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(92 citation statements)
references
References 10 publications
1
91
0
Order By: Relevance
“…Evaluations of educational programs aimed at adolescent mothers have significant prominence in the literature investigated (4) . However, it must be considered that, in general, the proposals of educational action and of assistance show dissociations, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Evaluations of educational programs aimed at adolescent mothers have significant prominence in the literature investigated (4) . However, it must be considered that, in general, the proposals of educational action and of assistance show dissociations, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen full reports [18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33] were included in the review. Two conference abstracts were excluded because of their limited information.…”
Section: Resultsmentioning
confidence: 99%
“…The demographic data varied in quantity and in categorization, making comparisons across studies difficult. The mean age of participants varied between 16.2 and 31.6 years, and studies tended to focus on women of specific ethnicity, such as white, 21,24,25,28,31 black, 19,22,32 Hawaiian, 23 or Hmong. 27 In 5 of the 6 studies that reported relationship status, the majority of participants were married or living with their partner.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Special and specific concern is necessary, as these mothers' degree of commitment in maintaining their children's growth is affected by the liability of their physical and psychological maturity. Moreover, several studies by researchers have suggested that social support plays an important role and is needed if adolescent mothers are to perform exclusive breastfeeding [4,6,10,12,15].…”
Section: Introductionmentioning
confidence: 99%